2019
DOI: 10.1101/787440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota differently contributes to intestinal immune phenotype and systemic autoimmune progression in female and male lupus-prone mice

Abstract: and castrated males. Overall, our work shows that microbiota-dependent pro-inflammatory immune response in the gut mucosa of females initiated at juvenile ages and androgen-dependent modest protection of males contribute to gender differences in the intestinal immune phenotype and systemic autoimmune progression in lupus-prone SNF1 mice.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 60 publications
(129 reference statements)
12
39
0
Order By: Relevance
“…Gut microbial composition were analyzed using fresh fecal samples collected at weeks 0, 4, and 7 of the experimental period (Figure 1). Individually, none of the NOR, HE, and HO groups showed intra‐group similarity in the fecal bacterial distribution patterns among these observation periods (Figure S4A) and were consistent with the previous reports 32‐34 . Moreover, Chao 1 analysis and the observed OTUs from 16S rRNA sequencing data revealed that the alpha diversity of the gut microbial community did not differ significantly among the aforementioned experimental groups at any measurement time points (weeks 0, 4, and 7; Figure S2A).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Gut microbial composition were analyzed using fresh fecal samples collected at weeks 0, 4, and 7 of the experimental period (Figure 1). Individually, none of the NOR, HE, and HO groups showed intra‐group similarity in the fecal bacterial distribution patterns among these observation periods (Figure S4A) and were consistent with the previous reports 32‐34 . Moreover, Chao 1 analysis and the observed OTUs from 16S rRNA sequencing data revealed that the alpha diversity of the gut microbial community did not differ significantly among the aforementioned experimental groups at any measurement time points (weeks 0, 4, and 7; Figure S2A).…”
Section: Resultssupporting
confidence: 90%
“…Individually, neither the SHAM nor the SHO group showed any intra‐group similarity in the fecal bacterial distribution patterns among weeks 0, 4, and 7 of the experimental period (Figure S4B), in agreement with the previous studies 32‐34 . Furthermore Chao‐1 analysis and the OTUs observed from 16S rRNA sequencing data showed that the alpha diversity of gut microbial communities did not differ significantly between SHAM and SHO groups at all time‐points of measurements (weeks 0, 4, and 7; Figure S2B).…”
Section: Resultssupporting
confidence: 90%
“…Importantly, anti-DNA antibodies of IgA class are found in the serum of patients with SLE 24 29 , suggesting that they may be of gut primed B cell origin. These reports along with our studies 16 , 17 showing pro-inflammatory immune phenotype and higher plasma cell frequency by lupus-prone female mouse intestine suggests the degree of IgA secretion in the gut lumen could show gender bias and may be indicative of lupus susceptibility and autoimmune progression. Nevertheless, the relationship between fecal IgA levels and gender bias in lupus is unknown.…”
Section: Introductionsupporting
confidence: 70%
“…We have demonstrated that minor dietary deviations alter the composition of gut microbiota and SLE in a mouse model 13 . We have also found that gut microbiota influences the autoimmune progression differently in lupus-prone male and female mice, leading to a gender bias in disease incidence 16 .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation